2014
DOI: 10.1007/s13277-014-1788-1
|View full text |Cite
|
Sign up to set email alerts
|

Do iron chelators increase the antiproliferative effect of trichostatin A through a glucose-regulated protein 78 mediated mechanism?

Abstract: Histone deacetylase (HDAC) inhibitors, such as trichostatin A (TSA), and iron chelators, including deferoxamine (DFO) and phenanthroline (PHEN), appear to have anticancer effects. We hypothesized that the HDAC inhibitors and iron chelators would be synergistic with their effect on breast cancer cell line MCF7, because the HDAC inhibitors increase glucose-regulated protein 78 (Grp78) and the iron chelators reduce its expression. Although the administration of TSA alone resulted in a dose-related decrease in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…However, GRP78 and GRP94 promoter regions were not hyperacetylated following TSA treatment. Previous studies have identified that there are HDAC1 response elements in the promoter region of GRP78 that function as negative regulation factors (17,18). This suggests that TSA may inhibit HDAC1 and induce GRP78 expression.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, GRP78 and GRP94 promoter regions were not hyperacetylated following TSA treatment. Previous studies have identified that there are HDAC1 response elements in the promoter region of GRP78 that function as negative regulation factors (17,18). This suggests that TSA may inhibit HDAC1 and induce GRP78 expression.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, p53 inactivation may be a driving factor for chemoresistance to TSA in HCT116 cells. Furthermore, a previous study has reported a combined effect of TSA with other factors, including iron chelators (18). Iron chelators promote binding between HDAC-1 and the GRP78 promoter region, which reduces GRP78 expression and promotes the chemotherapeutic effect of TSA.…”
Section: Discussionmentioning
confidence: 95%
“…Along with several other bis-and tris-hydroxamates, such as coelichelin (5), erythrochelin (1), vicibactin (3), aerobactin (6) and rhodochelin (4) (figure 1), and other members of the desferrioxamine complex (figure 2), desferrioxamine B (7) plays an important role in microbial iron uptake [8][9][10][11]. Iron is an essential nutrient for most forms of life because it plays a central role in several key metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting ferric-siderophore complexes are taken up by the microbial cells using ATP-dependent transport mechanisms and the iron is released via reduction or degradation of the ligand [15]. One well-studied example is the model antibiotic-producing actinobacterium Streptomyces coelicolor A3(2), which biosynthesizes and excretes coelichelin (5), desferrioxamine B (7) and desferrioxamine E (8) [11]. Distinct cell surfaceassociated lipoprotein receptor components of ATP-binding cassette (ABC) transporters (CchF and DesE, respectively) are used by S. coelicolor to import the ferricoelichelin and ferrioxamine complexes [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation